RGS6 Drives Spinal Cord Injury by Inhibiting AMPK Pathway in Mice. (25th April 2022) - Dao, Wenxin; Xiao, Zhe; Yang, Weize; Luo, Xiaomin; Xia, Hongxia; Lu, Zuneng
Abstract : Objective . Oxidative stress and inflammation play critical roles in the pathogenesis of spinal cord injury (SCI). Regulator of G protein signaling 6 (RGS6) is involved in controlling ROS generation and inflammatory response under different contexts. This study is aimed at investigating its role and underlying mechanism in SCI. Methods . Contusive SCI mouse models were generated, and lentiviral vectors were injected to silence or overexpress RGS6 in the spinal cord. To inhibit AMP-activated protein kinase (AMPK) activity, SCI mice were intraperitoneally injected with compound C (20 mg/kg) every two days. Oxidative and inflammatory markers were detected. Results . Spinal RGS6 expression was elevated upon SCI stimulation. RGS6 knockdown suppressed, while RGS6 overexpression aggravated oxidative stress, inflammation, and SCI in mice. Mechanistically, RGS6 elevation during SCI deactivated AMPK pathway, thereby exacerbating oxidative stress and inflammation in SCI mice. Conclusion . RGS6 is required for the initiation and progression of SCI, and knocking down RGS6 may provide promising therapeutic strategies for SCI patients.